Harmonic Analysis of Daily Mean Temperatures in Baghdad (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background:       Temperatures in tropical and subtropical latitudes of the northern hemisphere are characterized by periodic behavior. The distribution of temperature means follows a sine curve, which allows for its mathematical modeling as a function of time. Therefore, it is necessary to use experimental models of daily temperature means, this study aims to build an experimental model to calculate and estimate the daily mean in Baghdad.Materials and Methods:        Harmonic analysis used to detect the periodic pattern of daily mean temperature. Only three components of the Fourier series can explain the distribution pattern excluding the extreme temperatures and based on a time series of means measured in Baghdad for 14610 days extending from Jan 1980 to Dec 2020 retrieved from the archives of the Meteorological and Seismic Survey Authority.Results:        The harmonic analysis results showed a cyclic pattern with a frequency of (1.07cycle/year) approximately. Also showed that the experimental model was represented by a mathematically Fourier series of three components of sine and cosine functions leading to the calculation and estimation of daily means after adjusting the model parameters.Conclusions:         The validity of the model was measured using RMSE, MAE, and R2, and its outputs compared to independently measured data until April 2023, thus it can be concluded that the proposed model has a practically accurate performance with a minimum acceptable error in calculating and estimating the daily means in Baghdad.